Defects Observed in the Production of Thin –Walled Cast Products in a Sand – Clay Mold - Jamshidbek Khasanov; Nodir Turakhodjaev; Fakhriddin Makhmudov; Omonjon Yuldoshev; Abbos Abdukarimov (International Journal on Integrated Education, 2022)
In the article, the analysis of mechanical properties, analysis of micro – X – ray spectral phases is carried out in the study of the properties of the samples cut from the thin – walled lifting roof detail used in production enterprises. Also, the defects and shortcomings observed during the casting of thin – walled cast products in sand – clay molds using resource and energy – saving casting technologies, along with the analysis of model alloys, quantitative metallographic analysis and chemical analysis, are presented.